2009
DOI: 10.1007/s11605-009-0839-1
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of HSV-tk Suicide Gene Therapy Driven by the Grp78 Stress-Inducible Promoter in Esophagogastric Junction and Gastric Adenocarcinomas

Abstract: HSV-tk xwith ganciclovir suicide gene therapy results in significant cell killing in gastroesophageal junction and gastric adenocarcinoma cells both in vitro and in vivo, but complete tumor elimination only occurred with the gastric adenocarcinoma cell tumors. The most effective approach in this study used the Grp78 promoter in glucose-starvation stress conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Gene expression in 16 SAT samples and 16 VAT samples was measured by a two‐step multiplexed tandem PCR method (23). Primers for the genes of interest and NONO (non‐POU domain containing, octamer binding; NM_007363) as reference gene were designed using modified Primer 3 software (primer sequences available on request), as done previously (24,25). Given our a priori hypothesis that circulating inflammatory molecules that predict or are implicated in the pathogenesis of T2D are differentially expressed in adipose tissue, we selected the following genes of interest: adiponectin, TNFα, complement C3, retinol‐binding protein‐4 (RBP4), IL‐1α, IL‐1β, IL‐6, IL‐8, IL‐8 receptor, macrophage inflammatory protein (MIP), serum amyloid A, nuclear factor‐κB, cAMP response element–binding protein‐3.…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…Gene expression in 16 SAT samples and 16 VAT samples was measured by a two‐step multiplexed tandem PCR method (23). Primers for the genes of interest and NONO (non‐POU domain containing, octamer binding; NM_007363) as reference gene were designed using modified Primer 3 software (primer sequences available on request), as done previously (24,25). Given our a priori hypothesis that circulating inflammatory molecules that predict or are implicated in the pathogenesis of T2D are differentially expressed in adipose tissue, we selected the following genes of interest: adiponectin, TNFα, complement C3, retinol‐binding protein‐4 (RBP4), IL‐1α, IL‐1β, IL‐6, IL‐8, IL‐8 receptor, macrophage inflammatory protein (MIP), serum amyloid A, nuclear factor‐κB, cAMP response element–binding protein‐3.…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…As proof-of-principle, the Grp78 promoter driving the expression of the herpes simplex kinase suicide gene in a retroviral system results in eradication of sizable tumours 122,123 . Recently, systemic administration of a dual tumour-targeted phage containing the RGD tumour homing ligand and the Grp78 promoter, showed persistent transgene expression in vitro and significant killing of therapy resistant tumours in vivo 124 .…”
Section: Targeting Grpsmentioning
confidence: 99%
“…This constitutes an ideal gene therapy system to selectively kill tumor cells without affecting normal tissues. Azatian et al (77) have demonstrated that, compared with LTR-tk/GCV, GRP78-tk/GCV treatment resulted in complete tumor elimination in GC cells with no p53 mutations in vitro and in vivo (Table I).…”
Section: Grp78 Variants and Promoter Polymorphisms In Gcmentioning
confidence: 99%